Tapestry of fortunes [large type] : a novel - Berg, Elizabeth (Random House Large Print, 2013)
"Cecilia Ross is looking for a change. She has decided to take time off from her job as a successful motivational speaker and sell her home. She moves in to a beautiful old house in St. Paul, Minnesota, complete with a big front porch, a wild garden, a chef's kitchen--and three roommates. The four women are different ages, but all are feeling restless, and want to take a roadtrip to find again the people and things they miss. One woman wants to connect with a daughter she gave away at birth; another wants to visit her long-absent ex-husband; a third woman, a professional chef, is seeking new inspiration from the restaurants along the way. And Cecilia is looking for Dennis Halsinger, the man she never got over, who recently sent her a postcard out of the blue. This novel is classic Elizabeth Berg--a portrait of how women grow through the relationships that define them, and a testament to the power of female friendship"--